s.t. (Laptop on the pavement). : Mark Manders, Marije Langelaar. (Amsterdam : Roma Publications, 2002)
Book with various images collected in Arnhem. One of them is a painting by Mattijs van den Bosch, some others are photographs from bookpages.
Book with various images collected in Arnhem. One of them is a painting by Mattijs van den Bosch, some others are photographs from bookpages.
boek
Keywords: Manders, Mark; Willems, Roger; Langelaar, Marije